Potensi Antimikroba dan Toksisitas Minyak Atsiri yang Diisolasi dari Biji Jintan (Carum carvi L.) - Suryati Suryati; Emil Salim; Gustia Elizar (Jurnal Riset Kimia, 2022)
Caraway (Carum carvi L.) is one of the oldest medicinal plants found in various countries such as West Asia, North Africa, Pakistan, India, North America, Northern Europe, Iran, Russia, and Indonesia. This plant has been use for traditional medicines to treat digestive disorders, flatulence, colic in infants, headaches, coughs, hypertension, eczema, pneumonia, diabetes, scabies, mouthwash and as an antiseptic. This plant is reported to contain around 1-9% essential oil in the seeds with various components and potential as bioactive compounds. In this study, essential oils were isolated from caraway seeds and determined their chemical content as well as their antimicrobial and toxicity. Isolation of essential oils was carried out by hydrodistillation and analysis of the chemical components of the isolated essential oils was carried out using the Gas Chromatography-Mass Spectrometry (GC-MS) method. The results of the GC-MS analysis showed the presence of 35 compounds with four main compounds, namely carvone (62.54%), limonene (23.39%), and trans-dihydrocarvone (8.20%). The antimicrobial activity test was carried out using the disc diffusion method, which showed strong activity against Staphylococcus aureus at a concentration of ≥75%, and against the fungus Candida albicans. The results of the toxicity test using the Brine Shrimp Lethality Test (BSLT) method showed that caraway seed essential oil was low toxic against Artemia salina Leach shrimp larvae with an LC50 value 568.3292 mg/L.